2020
DOI: 10.1108/lht-12-2019-0239
|View full text |Cite
|
Sign up to set email alerts
|

Do proceedings papers in science fields have higher impacts than those in the field of social science and humanities?

Abstract: PurposeThis study aims to compare the impacts of proceedings papers in the fields of social science and humanities (SSH) and science.Design/methodology/approachThis study involved not only citations but also altmetric indexes to compare the impacts of proceedings papers among multiple disciplines with 1,779,166 records from Conference Proceedings Citation Index (CPCI) in the Web of Science (WoS) in the period of 2013–2017. The mean value, concentration ratio, Lorenz curves and correlation analysis are utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Chen et al (2021) studied the effect of interdisciplinary components' citation intensity on scientific impact. Yang and Qi (2021) investigated whether proceedings papers in science fields have higher impacts than those in social science and humanities (SSH). Bedogni et al (2022) further explored the correlation between the impact of scientific conferences and their venues.…”
Section: Research Trends Of Library and Information Science (Lis) And...mentioning
confidence: 99%
“…Chen et al (2021) studied the effect of interdisciplinary components' citation intensity on scientific impact. Yang and Qi (2021) investigated whether proceedings papers in science fields have higher impacts than those in social science and humanities (SSH). Bedogni et al (2022) further explored the correlation between the impact of scientific conferences and their venues.…”
Section: Research Trends Of Library and Information Science (Lis) And...mentioning
confidence: 99%
“…Total cites has a moderate positive correlation with the indicators values of journal discourse leading (0.361 ≤ r ≤ 0.765), indicating a significant overall consistency. Social media indicators are widely used to evaluate academic achievements, and many of them have a positive correlation between citation and online attention scores (Thelwall and Nevill, 2018;Huang et al, 2018;Lamba et al, 2021;Nuzzolese et al, 2019;Salajegheh and Dayari, 2019;Syamili and Rekha, 2017;Yang and Qi, 2021). Boetto et al (2021) used a sample of 212 scientific papers on COVID-19 and found a moderate correlation among traditional citations, social media citations, news and blog citations.…”
Section: Evaluation Of Discourse Leading For Integrating Altmetrics I...mentioning
confidence: 99%
“…Thus, altmetrics can be suitable to assess the impact of conference papers in a fast-moving research environment such that of Computer Science, as discussed in He and Han (2017). A recent study by Yang and Qi (2020) also reports that altmetrics indexes of conference papers in science fields are closely related to citations, reflecting the citation impact of proceedings papers.…”
Section: Related Workmentioning
confidence: 99%